THE ROLE OF CONTRIBUTORY NEGLIGENCE IN ALLEGED CASES OF MEDICAL NEGLIGENCE – A REVIEW - Kale, Satishchandra Purushottam; Mali, Mahaveer Prasad (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Contributory negligence is a key principle in medical negligence law, serving as a contributory defence that can partially shift the blame of the harm inflicted on the medical practitioner to the patient . As in any other common law country, contributory negligence is a well-known legal principle in India as well as several other countries, in that the measure of negligence can be affected by the complainant’s own act construed as negligence for reduction of compensation.